Anti-diabetic potential of peptide from P. niruri reveals through carbohydrate hydrolyzing enzyme inhibition assay - Md Zin, Noor Hasniza; Mohd Nail, Ainul Mardhiah (Zebline International Publishing, 2019)
Herb Phyllanthus niruri (P. niruri) is known to have various pharmacological functions including anti-diabetic properties. In this research, protein extracts from different plant parts (leave, fruit and stem) of P. niruri were investigated for their anti-diabetic potential through α-amylase and α-glucosidase enzyme inhibition assays. For the enzyme inhibition assay, fruit was found to have the highest inhibition percentage (90.0%) against α-glucosidase followed by leave (62.6%) and stem (38.4%). The similar patterns were also recorded for the α-amylase enzyme inhibition assay, in which, fruit showed the highest inhibition percentage (64.1%) followed by leave (33.3%) and stem (18.2%). The findings of this research suggest that fruit of P. niruri is a potential plant part with regards to antidiabetic properties since it exhibits the highest inhibition activity against both α-amylase and α-glucosidase enzyme compared to leave and stem.